A Multiple Biological Activities Cyclopeptide From Endophytic Fungus Phaeosphaeria Sp. XXH003 of the Marine Conus literatus - Lin, Ying‐ting; Liu, Jie; Huang, Zhou; Hu, An‐qi; Liu, Yu‐hang; Zhang, Zhi‐hao; Dong, Shuai (Chemistry & biodiversity, 2025)
ABSTRACT Chemical investigation of the endophytic fungus Phaeosphaeria sp. XXH003 isolated from Conus literatus was conducted. Eleven compounds were isolated and identified as ergosterol (1), β‐sitosterol (2), ergosterol peroxide (3), ergosta‐4,6,8(14),22‐tetraen‐3‐one (4), 1,1'‐oxybis(2,4‐di‐tert‐butylbenzene) (5), 5‐[(1S)‐1‐hydroxybutyl]‐6‐methyl‐2H‐pyran‐2‐one (6), quinolactacin C1/C2 (7/8), cyclodepsipeptide Sch 217048 (9), linoleic acid (10), and oleic acid (11), respectively. Their structures were determined by nuclear magnetic resonance and mass spectrometry. All compounds were isolated from Phaeosphaeria sp. for the first time, and the content of compound 9 was as high as 250 mg/kg rice culture medium. Compound 9 showed inhibitory effects on renal fibrosis at concentrations of 10 and 20 µM, leading to reduced expression of three types of fibrous‐related proteins in the human kidney 2 cells, including fibronectin, collagen I, and vimentin. At a concentration of 100 µM, compound 9 extended the lifespan of Caenorhabditis elegans by 14.77%. Compound 9 demonstrated both anti‐vesicular stomatitis virus and anti‐herpes simplex virus activity at a concentration of 15 and 20 µM. In addition, none of the compounds showed anti‐glioma cell line U87MG activity or lipotropic activity, and compounds 1, 2, 3, and 9 did not exhibit neuroprotective activity.